(untitled) (Journal of Computational Mathematics, 2005)
In this paper, we consider the cascadic multigrid method for the mortar P_1 nonconforming element which is used to solve the Poisson equation and prove that the cascadic conjugate gradient method is accurate with optimal complexity.